Business Information Systems Workshops BIS 2009 International Workshops, Poznan, Poland, April 27-29, 2009, Revised Papers - Abramowicz, Witold; Flejter, Dominik (Lecture Notes in Business Information Processing, 2009)
This book constitutes the proceedings of the nine workshops that were organized in conjunction with the Business Information Systems Conference, BIS 2009, taking place in Poznan, Poland, on April 27-29, 2009. The 34 papers presented were carefully reviewed and selected from 72 submissions. In addition, the volume contains the BIS 2009 keynote speech and two invited speeches presented at the workshops LIT and ECONOM/Enterprise X.0. The topics covered are DeepWeb (ADW), applications and economics of knowledge-based technologies (AKTB, ECONOM), service-oriented architectures (SDS-SOA), legal IT (LIT), social Web and Web 2.0 (SAW, Enterprise X.0), e-learning (EeLT), and enterprise systems in higher education (ESHE).